1984
DOI: 10.21273/jashs.109.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Litchi Growth and Compositional Changes during Fruit Development

Abstract: The changes in litchi (Litchi chinensis Sonn.) growth and composition were studied in 4 cultivars; ‘Groff’ in Hawaii, and ‘Shui Dong’, ‘Gui Wei’, and ‘Mei selection’ in Guangdong, China. Fruit and aril growth showed a sigmoidal pattern while skin growth was slower and more linear. Aborted seeds in Groff and Gui Wei ceased growth early in the log growth phase. Normal seeded cultivars showed seed growth paralleling skin growth. Skin chlorophyll began to decrease logarithmically soon after the start of fruit grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…However, the organic acids in 'Huanongzao' and 101 F 1 hybrids in this study were mainly malic acid, oxalic acid, and citric acid, but fumaric acid was also detected. The research has shown that the acids in lychee were mainly malic acid, succinic acid, and citric acid [19], although Hu et al [20] suggested malic acid and tartaric acid. In this study, the organic acids in 'Ziniangxi' were mainly malic acid and citric acid; gallic acid was undetected.…”
Section: Discussionmentioning
confidence: 99%
“…However, the organic acids in 'Huanongzao' and 101 F 1 hybrids in this study were mainly malic acid, oxalic acid, and citric acid, but fumaric acid was also detected. The research has shown that the acids in lychee were mainly malic acid, succinic acid, and citric acid [19], although Hu et al [20] suggested malic acid and tartaric acid. In this study, the organic acids in 'Ziniangxi' were mainly malic acid and citric acid; gallic acid was undetected.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of fruit and arils shows a sigmoidal pattern, while the growth is slower and more linear (Figure 1a). Rapid growth is principally due to an increase in aril tissue (Paull et al., 1984). Fruit length increased up to the 1 7t h week from anthesis, while width and weight increased continuously.…”
Section: Postharvest Physiologymentioning
confidence: 99%
“…Total sugars increase in aril from 3% to 16% during the rapid growth period. Aril acidity decreases over 2 weeks in the middle of fruit growth (Paull et al., 1984). Titratable acidity (TA) is mainly due to malic acid.…”
Section: Postharvest Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Uno de los alimentos en los que lo recubrimientos han encontrado su uso más amplio es en la conservación de frutos ya que son altamente perecederos y presentan un metabolismo activo durante el almacenamiento. El litchi (Litchi chinensis Sonn) es una fruta de fácil descomposición, no climatérica valorada comercialmente por su sabor exótico (Paul et al, 1984). El fruto litchi pertenece a la familia Sapindaceae, hay varias variedades de litchi con diversos colores, pero los cultivares rojos son los más importantes para los mercados internacionales.…”
Section: Introductionunclassified